Management of Menstrual Disorder in Adolescent Girls with Intellectual Disabilities: A Blessing or a Curse?. (11th July 2018) - Nurkhairulnisa, Abu Ishak; Chew, Kah Teik; Zainudin, Ani Amelia; Lim, Pei Shan; Shafiee, Mohamad Nasir; Kampan, Nirmala; Wan Ismail, Wan Salwina; Grover, Sonia; Nur Azurah, Abdul Ghani
Abstract : Objective . This study aims to describe the menstrual pattern and menstrual care of girls with intellectual disabilities and to evaluate the impact of menstruation and awareness of parents/guardians on girls with intellectual disabilities. Methodology . Parents/guardians of girls aged 9–17 years with known intellectual disabilities who attended a scheduled public forum and Paediatrics and Adolescent Gynaecology Clinic (PAC) were recruited in a questionnaire-based study. Results . A total of 123 parents/guardians with a mean age of 41.83 ± 5.45 years completed the questionnaire. The mean age of girls with intellectual disabilities was 12.28 ± 2.78 years, and the mean menarcheal age was 11.12 ± 1.76 years. Only 53 (43.1%) parents/guardians were aware of availability of menstrual suppression. Parents/guardians with lower family income (OR = 0.00; 95% CI = 0.00–0.20), unable to manage menses (OR = 0.03; 95% CI = 0.00–0.61), and moderate severity of menses (OR = 0.01; 95% CI = 0.00–1.21), were associated with seeking medical help on menstrual suppression. The factors associated with parents/guardians requesting for sterilization were lower family income (OR = 0.02; 95% CI = 0.00–0.36) and concern about sexual abuse (OR = 0.25; 95% CI = 0.06–0.39). Conclusion . Menstrual pattern in girls with intellectual disabilities is similar to those without disabilities. Parents/guardians' knowledge and awareness on menstrual suppression were still lacking.